LEGAL PROTECTION OF PUBLIC MORALITY - AXIOLOGY OF LEGAL RELATIONS AND LAW ENFORCEMENT ACTIVITIES IN UKRAINE: A MODERN COMPARATIVIST APPROACH - Ruvin, Sergiy (Socio-economic relations in the digital society, 2023)
The purpose of the article is to study the modern comparative approach to determining the influence of the level of the legal protection of public morality on the axiological component of legal relations and law enforcement activities in Ukraine within the framework of theoretical and legal discourse. As a result of the conducted analysis, it is necessary to state that the axiology of legal relations in society in the general system of coordinates and interaction with other types of social relations is permanently permeated by the categories of social morality. At most, morality is a system of principles, and a spindle of social principles, which permeates all types of social relations without exception, is the starting point for their generally human and philosophical qualification, a marker of compliance with the needs of modernity. The article establishes that law enforcement activity is a special type of social relations, since on the one hand it interacts prominently with society, the widest circle of legal subjects, almost without exception, on the other hand, it is a narrow-profile, specialized activity of persons authorized to do so. Therefore, it was established that the law enforcement sphere is at the same time the so-called issuer, creator, and developer of moral principles, as rule narrow-branch ones, which, at the same time, clearly intersect and interact with general social principles, complementing each other, penetrating into other spheres of sectoral social relations, supplementing them, changing, transforming legal validity, etc. It was established that the level of public morality of law enforcement officers directly affects the state of compliance with public morality by civil society, and vice versa: the level of public morality of society draws a demarcation line for the system of permissible worldview and behavioral principles of law enforcement agencies. At most, it seems quite obvious that one of the most effective means of acceptance by law enforcement agencies of values, principles, ideas, and norms of public morality is the maximum integration of law enforcement agencies into the social, human plane, their immersion in the urgent needs of society, its requests, the spirit of the law as much as possible, to which it aspires. At the same time, the so-called "humanization" of law enforcement agencies is, on the one hand, a demand of society for the law enforcement system and, at the same time, a guarantee of the protection of public morality, because only humanized law enforcement agencies are able to ensure and guarantee the specified process.